The effects of fermented pineapple residue on growth performance, meat quality, and rumen microbiota of fattening Simmental bull - Deng, Ming; Xiao, Zupeng; Liu, Guangbin; Sun, Baoli; Guo, Yongqing; Zou, Xian; Liu, Dewu; Yang, Zhenwei; Li, Yaokun (Frontiers in Microbiology, 2022)
In this study, silage Pennisetum sinese Roxb-based diet was replaced with fermented pineapple residue (FPR) at the replacement ratio of 0% (CON), 25% (T25), and 50% (T50) in fattening Simmental bulls for 30 days to evaluate the effects of FPR on growth performance, serum indexes, and ruminal characteristics. A total of 30 Simmental bulls (546 ± 44 kg initial BW) were allocated to three groups according to a completely randomized design. On day 30, the slaughter performance and meat quality were determined. Rumen fluids were collected for analyzing the rumen fermentation parameters and microbiota composition on day 30. The results showed that the average daily weight gain increased (P < 0.05) as the proportion of FPR rose. Within treatments, the T25 group reached more profit (5.34 RMB per day per bull) than CON while T50 was 3.69. The content of crude fat, cysteine, and proline in the muscle of T50 increased significantly (P < 0.05). The amounts of tyrosine, proline, and phenylalanine were significantly increased in the T25 (P < 0.05). The beta diversity analysis showed significant differences among the rumen bacterial flora of each group (P < 0.05). In the T25 group, the relative abundance of Spirochaetes decreased significantly (P < 0.05). The relative abundance of Lachnospiraceae_bacterium_RM44 was significantly lower (P < 0.05). Thus, FPR could improve the growth performance, economic benefits, and meat quality without adverse effects on ruminal characteristics.